Effect of dexmedetomidine on recovery profile of patients undergoing anterior cervical discectomy and fusion - Varun Jain; Arvind Chaturvedi; Mihir P Pandia; Parmod K Bithal (Wolters Kluwer Medknow Publications, 2019)
Background and Aim: Smooth and rapid emergence and extubation, with minimal coughing, is desirable after cervical spine surgery to facilitate early neurological examination. The present study investigated the effect of dexmedetomidine as an intraoperative anesthetic adjuvant on postoperative extubation and recovery profile in patients undergoing anterior cervical discectomy and fusion (ACDF) surgery. Material and Methods: Sixty-four, American Society of Anesthesiologist I or II adult patients (age 18-60 years) were randomized in this placebo-controlled, double-blind study. In group D, dexmedetomidine was started at 0.2 μg/kg/h after a loading dose of 1 μg/kg before induction and in group P, volume and infusion rate-matched normal saline was used. Perioperative hemodynamics, intraoperative anesthetic consumption, and postoperative recovery profile were observed. Results: Thirty-one patients in each group successfully completed the study. Time to emergence (6.9 min vs 10 min, P < 0.001), time to extubation (8.5 min vs 12.2 min, P = 0.002), and time to achieve modified Aldrete score ≥9 (5 min vs 10 min, P < 0.001) were earlier in group D compared to group P, respectively. Pain score at extubation was lower (0 vs 20) and time for first analgesic was longer (50 min vs 15 min) in group D compared to group P. Coughing at extubation was comparable in both the groups. One patient in group D had severe postextubation bradycardia. Conclusions: Intraoperative use of dexmedetomidine at the lowest recommended dosage in adults undergoing ACDF surgery results in a favorable recovery profile with reduced emergence/extubation time and postoperative pain, but similar incidence of coughing.